OP0178 Fibroblast priming is common to many sites, and psoriatic skin fibroblasts may acquire inflammatory memory. (15th June 2017) - Crowley, T; O'Neil, JD; Adams, HR; Kragstrup, TW; Filer, A; Buckley, CD; Clark, AR
Abstract : Background: Rheumatoid arthritis (RA) is a common chronic inflammatory disease of the joints. Whilst the autoimmune element continues to be studied intensely, it is evident that the innate inflammatory response propagates the disease. Fibroblast-like synoviocytes (FLS) are the most abundant stromal cell in the synovium. FLS from RA joints are markedly different from their healthy counterparts in their inflammatory characteristics. RA FLS exhibit a form of inflammatory memory named priming. Prolonged exposure to TNFα induces an augmented chemokine response to challenges with interferons [1]. Fibroblast priming leads to significantly augmented IL6, CCL5 and CXCL10 responses to a second challenge by TNFα, with a coincident prolonged NFκB nuclear localization (manuscript in press). Objectives: We wished to assess whether fibroblasts from sites other than the synovial joint would also exhibit this primed response to second challenge. Methods: Fibroblasts from the joint, skin, lung, tonsil, bone marrow and gum were stimulated with 10ng/ml TNFα for 24h, before the conditioned medium was removed and the cells were washed free of stimulus. Cells were rested for 24h before once again being washed and stimulated with 10ng/ml TNFα for a further 24h. The conditioned medium was removed and secreted mediators compared between first and second response to stimulus. Transcription and intracellular signalling at time points within each challenge were also determined. Results: Synovial, lung and tonsil fibroblasts augmented IL6 secretion in response to the second TNFα challenge. RA bone marrow-derived fibroblasts varied in their exhibition of priming. Skin fibroblasts from patients undergoing cosmetic surgery and a gingival sample from non-chronic inflammation displayed no evidence of IL6 priming. Fibroblasts from the skin of psoriasis (Ps) patients mounted a primed response that was significantly augmented compared to their first response to TNFα, and significantly higher than the second response of healthy skin. This augmented response matches that of FLS, as IL6 but not IL8 was increased. This pattern was also matched by gum fibroblasts from periodontitis. Mechanistically the Ps skin fibroblasts match FLS, in that NFκB nuclear localization is prolonged in the second challenge compared to the first. Conclusions: We have shown that inflammatory memory in the form of IL6 priming occurs in fibroblasts from a variety of anatomical sites with diverse functions. Its prevalence implies a shared phenomenon, but the variation between sites suggests a specific role required in some tissues and not others. The finding that Ps skin fibroblasts acquire this memory response may point towards a pro inflammatory mechanism that contributes to psoriatic diseases, including psoriatic arthritis. Our data may help to explain why an estimated 30% of psoriasis patients go on to develop psoriatic arthritis [2]. References: Sohn, C., et al., Prolonged TNFα primes fibroblast-like synoviocytes in a gene-specific manner by altering chromatin. Arthritis Rheumatol, 2014. Mease, P.J., et al., Prevalence of rheumatologist-diagnosed psoriatic arthritis in patients with psoriasis in European/North American dermatology clinics. J Am Acad Dermatol, 2013. 69(5): p. 729–35. Disclosure of Interest: None declared